Business Model Development at Multifinance Agency (Study of Keday Adira Finance) - Safira Aulia Rosalini; Idqan Fahmi; Arief Safari (School of Business, IPB University (SB-IPB), 2024)
Every business required strategic planning to face the competition and to grow in their environment. The relationship between consumer and company was affected by several things, one of them was to make an agent as a connection between consumer and company. The relationship sometimes created a conflict of interest such as moral hazard and adverse selection. Keday Adira was an external agent with MSMEs background that could offer Adira Finance’s product to consumers. The purpose of this research was to identify existing model business, analyze alternative strategy and define priority strategy to design Keday Adira’s Business Model Canvas recommendation. This research used the IPA method with 100 respondents to define priority variables on business model, and continued with IFE, EFE, SWOT, and QSPM analysis. The result of this research showed that channels and key activities were priority elements to be improved. Keday Adira was on hold and maintained position and generated ten alternative strategies. Those ten alternative strategies were carried out using QSPM methods to produce a sequence of strategies that could be implemented. Those strategies impacted on the Keday Adira’s Business Model Canvas on value propositions, customer relationship, channel, key activities, key resources, and revenue streams block. Keywords: business model canvas, business model development, strategic management, SWOT